On the Unilateralism of Physicalism and the Universality of Informationism - Mingyi Chen; Zongrong Li (Computer Sciences & Mathematics Forum)
The Call for Papers of IS4SI points out that paradigms from the disciplines of information and physics, respectively, reflect very different scientific viewpoints and methodologies. The sponsor and organizer selected “Paradigm Changes in Information Discipline” as the theme of the conference. The authors of this paper believe that the key to achieving the transformation of the “scientific paradigm” from a physical discipline to an information discipline lies in revealing and identifying one of the most fundamental propositions: recognizing the one-sidedness of “physicalism” and the universality of “informationism”, and accepting the world view, scientific view, values, and methodology of theoretical information science. Therefore, the main content of this paper discusses the one-sidedness of physicalism, the universality of informatics, and propose the promotion of the zeitgeist of the information age.